Comprehensive insights into the interactions of dicyclohexyl phthalate and its metabolite to human serum albumin. (September 2021) - Lv, Xiaolan; Jiang, Zheng; Zeng, Guofang; Zhao, Sujuan; Li, Na; Chen, Fengping; Huang, Xiaojian; Yao, Jia; Tuo, Xun
Abstract: Phthalate esters (PAEs) are a type of persistent organic pollutants and have received widespread concerns due to their adverse effects on human health. Dicyclohexyl phthalate (DCHP) and its metabolite monocyclohexyl phthalate (MCHP) were selected to explore the mechanism for interaction of PAEs with human serum albumin (HSA) through molecular docking and several spectroscopic techniques. The results showed that DCHP/MCHP can spontaneously occupy site I to form a binary complex with HSA, and DCHP exhibited higher binding affinity to HSA than MCHP. At 298 K, the binding constants (Kb ) of DCHP and MCHP to HSA were 24.82 × 10 4 and 1.04 × 10 4  M −1, respectively. Hydrogen bonds and van der Waals forces were the major driving forces in DCHP/MCHP–HSA complex. The presence of DCHP/MCHP induced the secondary structure changes in HSA, and the pi electrons of the benzene ring skeleton of DCHP/MCHP played a key role in this binding processes. Exposure of DCHP/MCHP to TM4 cells revealed that interactions between PAEs and serum albumin can affect their cytotoxicity; DCHP showed higher toxicity than MCHP. The binding affinity of PAEs with HSA may be a valuable parameter for rapid assessment of their toxicity to organisms. Graphical abstract: Image 1 Highlights: 1.DCHP/MCHP binding to HSA via hydrogen bonds and van der Waals. 2.The binding affinity of DCHP to HSA was higher than MCHP. 3.The secondary structure changes of HSA was induced by DCHP/MCHP. 4.The electronic structure of the benzene ring plays a critical role in the binding process. 5.The association constant of PAEs–HSA complex is a valuable parameter to assess PAEs cytotoxicity.